An ethical framework for complementary and alternative therapists - Stone, Julie, LL. B. (Routledge, 2002)
Julie Stone demonstrates that ethical issues are no less relevant to complementary and alternative medicine (CAM) practitioners than to any other group of health professionals and she provides a detailed framework for practitioners thinking constructively about how ethics impact on their work.